Monitoring as a Tool for Improvement of Modern Regional Anti-Corruption Policy in Russia - KAZACHKOVA, Zemfira M.; KOZLOVA, Elena B. (Journal of Advanced Research in Law and Economics, 2020)
Despite an extensive collection of specialized literature on anti-corruption field, including in the Russian segment of the study of these phenomena, issues of anti-corruption monitoring are not the dominant branch of modern special issues. However, it is this aspect that allows us to discover the real effect of managerial decisions of different anti-corruption agencies. Russia is the largest federal state in which the influence of regional anti-corruption strategies and programs is heterogeneous. Regions are rapidly gaining experience, identifying critical zones, corruption traps. In this sense, the generalization of this experience, the extrapolation of the results is a scientific task with a serious future perspective.